Preparation of Serbia for implementation of Chapter 22 in the field of regional policy - Živojinović Sonja (Ekonomski Signali, 2020)
Regional policy is the EU's main instrument for investing in sustainable and inclusive economic growth. Member States are responsible for its implementation, which requires adequate administrative capacity and sound financial management. When Serbia becomes a member of the EU, it will have at its disposal many times more funds from the EU structural funds than the ones it currently receives, and for the use of which it must prepare before joining the Union. Member States must respect EU law when selecting and implementing projects, in areas related to regional policy and Structural Instruments. Member States must also establish the institutional framework, organizational arrangements and necessary organizational arrangements to prepare supporting documents. This implies the establishment of all structures at the national and regional level required by EU regulations and standards. This Chapter 22 has a double meaning: it is important in itself, because through the negotiations on this Chapter it must be proven that we are in the mood to establish good and sufficient capacities for the use of EU Cohesion Policy. At the same time, Serbia is thus preparing to be an equal participant in the Union's Cohesion Policy, as well as all other member states.